2013
DOI: 10.3390/molecules18078319
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Antifolate Activity of Synthetic Tea-Derived Catechins

Abstract: Novel tea catechin derivatives have been synthesized, and a structure-activity study, related to the capacity of these and other polyphenols to bind dihydrofolate reductase (DHFR), has been performed. The data showed an effective binding between all molecules and the free enzyme, and the dissociation constants of the synthetic compounds and of the natural analogues were on the same order. Polyphenols with a catechin configuration were better DHFR inhibitors than those with an epicatechin configuration. Antipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Catechins are hydroxy and gallate substitutions of the flavan-3-ol structure, each with relative bioactive effects [32]. Chemotherapeutically, the gallocylated catechins, GC, EGC, GCG, and EGCG are noted to possess the most chemotherapeutically active role [33][34][35][36][37].…”
Section: Bioactive Rolementioning
confidence: 99%
“…Catechins are hydroxy and gallate substitutions of the flavan-3-ol structure, each with relative bioactive effects [32]. Chemotherapeutically, the gallocylated catechins, GC, EGC, GCG, and EGCG are noted to possess the most chemotherapeutically active role [33][34][35][36][37].…”
Section: Bioactive Rolementioning
confidence: 99%
“…They prevent against various pathological disorders and attention has been paid due to their pharmacological effects such as anticancer, anti‐oxidation, anti‐aging, antibacterial and antiviral activities, enzyme inhibition or activation . Several studies have reported that the potential effects of flavonoids on the enzyme inhibition or activation are related with their chemical structure like the number, positions, and types of substitutions . This study was aimed to investigate potential effects of some flavonoid derivatives with similar chemical structure on human PKM2.…”
Section: Introductionmentioning
confidence: 99%
“…This is highlighted by some authors, as Ottaviani et al (2011), who report that (-)-epicatechin is the only stereoisomer capable of mediating a significant arterial dilation between some tested catechins. Other activities of these molecules when present in biological systems have been reported (DONOVAN et al, 2006;SAEZ-AYALA et al, 2013;SIRK et al, 2009;TAYLOR;HAMILTON-MILLER;STAPLETON, 2005).…”
Section: Chemical Concerns Regarding Tanninsmentioning
confidence: 93%